Fluorescent antibacterial acrylic emulsion as well as preparation method and application thereof

By using fluorescent antibacterial acrylic emulsion in antibacterial coatings, combined with the technology of synergistic sterilization of ROS and cationic quaternary ammonium salts in AIE fluorescent molecules, the existing antibacterial coatings have solved the problems of environmental pollution, weakening antibacterial capabilities and complex detection, and achieved a more lasting, environmentally friendly and simple detection of antibacterial effects.

CN119859211APending Publication Date: 2025-04-22THE NAVAL MEDICAL UNIV OF PLA

Patent Information

Application Number
CN202510187693.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing antibacterial coatings have problems such as environmental pollution, gradual weakening of antibacterial capabilities and complex detection, and the single antibacterial method has limited effect.

Method used

Fluorescent antibacterial acrylic emulsion is used, which consists of acrylic monomers, AIE fluorescent small molecules, antibacterial quaternary ammonium monomers, non-ionic emulsifiers, cationic emulsifiers, initiators, stabilizers and deionized water. The ROS and cationic quaternary ammonium salts are produced through AIE fluorescent molecules to synergize the antibacterial performance detection method of coatings.

Benefits of technology

It achieves environmental protection, extends the antibacterial life of the coating, simplifies the antibacterial performance detection process, and provides a more lasting and environmentally friendly antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859211A_ABST
    Figure CN119859211A_ABST
Patent Text Reader

Abstract

The invention provides a fluorescent antibacterial acrylic emulsion as well as a preparation method and application thereof. The fluorescent antibacterial acrylic emulsion comprises an acrylic monomer, AIE fluorescent micromolecules, an antibacterial quaternary ammonium salt monomer, a nonionic emulsifier, a cationic emulsifier, an initiator, a stabilizer and deionized water. The cosolvent of the water-based acrylic coating is water, no VOC (volatile organic compound) is discharged when the water-based acrylic coating is used, and harm to the environment and human bodies is reduced to the minimum; meanwhile, the antibacterial coating is prepared in a positive ion and ROS joint antibacterial mode, and the antibacterial effect is more excellent; and a convenient detection method for reflecting the change of the antibacterial property of the coating through the fluorescence change of the coating avoids the trouble of professional biological detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial coatings, and in particular relates to a fluorescent antibacterial acrylic emulsion and a preparation method thereof, and also relates to an antibacterial coating containing the same and a preparation method thereof. Background Art

[0002] The antibacterial principles of existing antibacterial coatings are mainly divided into two categories. One is to add metal cations containing antibacterial ingredients or various inorganic / organic monomers to directly kill microorganisms; the other is to create a low surface energy or renewable surface to prevent the adhesion of microorganisms. However, both methods will release toxic agents that are easy to cause harm to the environment, and a single antibacterial method has limited effect, which can easily make bacteria resistant, causing the antibacterial ability of the coating to gradually weaken or even completely fail. In addition, after curing and film formation, the test method for evaluating the antibacterial performance of the coating is complicated, so a simpler and more intuitive method is needed to evaluate the effectiveness of the antibacterial coating.

[0003] Aggregation-induced emission (AIE) refers to the situation where fluorescent molecules do not emit light or emit light weakly in a uniformly dispersed low concentration state, but emit strong light when the solubility decreases or the concentration reaches a certain limit. This is because such molecules have multiple aromatic rings and a propeller-shaped structure. As the concentration increases, the distance between molecules decreases, the molecular vibration / rotation is restricted, and multiple aromatic rings form a relatively stable conjugated structure in a plane. Such a structure is conducive to receiving and emitting energy through optical channels. At the same time, the restricted movement leads to a reduction in the thermal dissipation of energy, so its fluorescence intensity is enhanced. Aggregation-induced emission technology has been widely used in optoelectronic devices, biomedicine and new materials.

[0004] ROS (Reactive Oxygen Species) are a class of molecules with strong oxidizing properties, the most common of which is hydrogen peroxide. , superoxide anion , hydroxyl radical (·OH), etc. The antibacterial principle of ROS is as follows: ROS can directly react with the cell membrane, protein and nucleic acid of pathogens, resulting in the destruction of their structure and function; ROS can cause DNA chain breaks or mutations, which will interfere with the replication and repair process of pathogens, and ultimately lead to their death or dysfunction; ROS can bind to key enzymes of pathogens or oxidize their active sites, inhibiting their metabolic activities. For example, some ROS will inhibit the respiratory chain enzymes of bacteria, thereby affecting their energy production;

[0005] Cationic Quaternary Ammonium Compounds (QACs) are a type of commonly used antimicrobial agent, widely used in disinfectants and cleaning products. Their antimicrobial principles mainly include the following aspects:

[0006] (1) Damage to cell membranes: Cationic quaternary ammonium salts have a positive charge, which enables them to interact with the negatively charged phospholipid molecules on the bacterial cell membrane; the positive charge of quaternary ammonium salts destroys the integrity of the cell membrane and increases membrane permeability. Cell membrane rupture or instability leads to leakage of intracellular substances, ultimately leading to bacterial death. (2) Damage to intracellular enzyme systems: Cationic quaternary ammonium salts can interfere with various enzyme systems in bacterial cells, including metabolic enzymes and respiratory enzymes. They inhibit the function of enzymes by binding to the active sites of these enzymes or changing their spatial structures, thereby affecting bacterial metabolism and growth. (3) Triggering intracellular oxidative stress: Cationic quaternary ammonium salts can cause intracellular oxidative stress reactions and increase the generation of reactive oxygen species (ROS). These reactive oxygen species can cause oxidative damage to important molecules in the cell, such as proteins, lipids, and nucleic acids, thereby promoting bacterial death. In addition, there are also principles such as interfering with protein synthesis, changing intracellular ion balance, and synergistic bactericidal effects.

[0007] There is no antibacterial coating combining the three technologies in the prior art. Summary of the invention

[0008] The present invention aims at the above problems and provides a fluorescent antibacterial acrylic emulsion, a preparation method thereof and its application in the preparation of antibacterial coatings. The present invention aims to solve the following three problems: first, to solve the environmental damage caused by the existing addition of antibacterial agents and the threat to human health; second, to solve the limitation of a single antibacterial method and enhance the sterilization ability of the coating by using AIE fluorescent molecules to generate ROS and cationic quaternary ammonium salts for synergistic sterilization; third, the traditional coating antibacterial performance detection method is complicated and cannot provide effective information on the antibacterial performance of the coating in a timely manner in conventional use scenarios.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] In a first aspect, the present invention provides a fluorescent antibacterial acrylic emulsion, comprising acrylic monomers, AIE fluorescent small molecules, antibacterial quaternary ammonium salt monomers, nonionic emulsifiers, cationic emulsifiers, initiators, stabilizers and deionized water.

[0011] In terms of content, by weight, the acrylic monomer composition is as follows: 25-30 parts of methacrylate MMA, 12-16 parts of 2-ethylhexyl acrylate 2-EHA, and 1.5%-2% of hydroxyethyl acrylate HEA;

[0012] The AIE fluorescent small molecule is 1‰-5‰ of the total amount of acrylic acid monomer, 2-5 parts of antibacterial quaternary ammonium salt monomer, 1-2 parts of non-ionic emulsifier, 1-2 parts of cationic emulsifier, the initiator accounts for 0.8%-1.2% of the total mass of all monomers (acrylic acid monomer, AIE fluorescent small molecule, antibacterial quaternary ammonium salt monomer, non-ionic emulsifier, cationic emulsifier, stabilizer), 1-2 parts of stabilizer, and 90-100 parts of deionized water; the total mass ratio of all components is 100%.

[0013] Preferably, the antibacterial quaternary ammonium salt monomer is selected as the cationic monomer from an 80% aqueous solution of acryloyloxyethyl trimethyl ammonium chloride;

[0014] The nonionic emulsifier is selected from any one or more combinations of OP-10, isomeric tridecanol polyoxyethylene ether (E1309), and 2535 nonionic emulsifier;

[0015] The cationic emulsifier is selected from any one of hexadecyl dimethyl benzyl ammonium chloride and hexadecyl trimethyl ammonium bromide;

[0016] The stabilizer is selected from disodium hydrogen phosphate or dipotassium hydrogen phosphate, or a combination of the two;

[0017] The initiator is selected from azobisisobutylamidine hydrochloride V50 (AIBA). AIBA is a water-soluble azo initiator used to replace the persulfate system and is suitable for the synthesis of cationic polymers.

[0018] The second aspect of the present invention provides a method for preparing a fluorescent antibacterial acrylic emulsion, comprising the following steps:

[0019] (1) Weigh some nonionic emulsifier, cationic emulsifier, initiator, and deionized water and stir them evenly to prepare the emulsifier part of the pre-emulsion;

[0020] (2) Weigh all the methyl methacrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate and AIE fluorescent small molecule, mix them evenly, and then add them dropwise to the emulsification in step (1). After the addition is completed, stir at a high speed until the pre-emulsion presents a stable light yellow color and does not delaminate after standing for a period of time, thereby completing the preparation of the pre-emulsion;

[0021] (3) Weigh a certain amount of deionized water, stabilizer, remaining nonionic emulsifier and cationic emulsifier, and part of the initiator to prepare a primer solution. After mixing the solution except the initiator evenly, add it into the reaction container, heat it to 75°C, and condense it under reflux. Add 10% of the total weight of the pre-emulsion, and start adding the initiator dropwise at the same time. Observe whether the reaction container turns blue.

[0022] (4) After the emulsion in the reaction container turns blue in step (3), the remaining pre-emulsion and the initiator mixed aqueous solution prepared from the initiator and the antibacterial quaternary ammonium salt monomer are added dropwise at a uniform rate, and the temperature is raised to 78° C. and maintained constant during the process;

[0023] (5) After the addition is completed, the temperature is maintained constant and the reaction is continued for 30 minutes, then the temperature is increased to 85°C and the reaction is continued for 30 minutes;

[0024] (6) After the reaction is completed, the system is cooled to below 40°C and the material is discharged to obtain a fluorescent cationic acrylic emulsion. The gel in the emulsion obtained from the experiment is filtered through a filter, weighed, and the gel fraction is calculated.

[0025] Preferably, deionized water accounts for 15%-20% of the total water in the pre-emulsion, 50%-60% of the total water in the primer, and 22%-30% of the total water in the initiator mixed aqueous solution;

[0026] The emulsifier in the pre-emulsion accounts for 70-75% of the total emulsifier, and the emulsifier in the primer accounts for 25-30% of the total emulsifier;

[0027] The initiator in the pre-emulsion accounts for 30-35% of the total amount of initiators, the initiator in the primer accounts for 15-20% of the total amount of initiators, and the initiator in the initiator mixed aqueous solution accounts for 50% of the total amount.

[0028] More preferably, in step (1), 71.4% of nonionic emulsifier, 71.4% of cationic emulsifier, 32.5% of initiator and 20% of deionized water are weighed to prepare the emulsifier part of the pre-emulsion.

[0029] In step (2), the emulsification dropwise addition process lasts for about 20 minutes. After the dropwise addition is completed, the mixture is stirred at 800 r / min or more for 30 minutes until the pre-emulsion exhibits a stable light yellow color and does not stratify when left to stand for more than 30 minutes, thereby completing the preparation of the pre-emulsion. In this step, the pre-emulsification speed needs to be high at 800 r / min or more to avoid stratification of the pre-emulsion.

[0030] In step (3), 52% of deionized water, all stabilizers, remaining nonionic emulsifiers and cationic emulsifiers are weighed, mixed evenly, added to a reaction vessel, heated to 75°C, and condensed and refluxed; 10% of the total weight of the pre-emulsion is added, and at the same time, a solution prepared with 17.5% initiator is started to be added dropwise, and the reaction vessel is observed to see whether it turns blue. In this step, the speed of the agitator is always controlled at 300-350 r / min after the pre-emulsion is added to the reactor until the reaction is completed.

[0031] If there is still no sign of blueing 20 minutes after the addition of the pre-emulsion, the temperature of the reactor is raised by 1-2°C and the initiator aqueous solution is added dropwise at a rate of about 0.2 ml / min until the solution turns blue and the next step is started.

[0032] In step (4), the mixed aqueous solution of the initiator and the antibacterial quaternary ammonium salt monomer is prepared by the remaining 50% of the initiator, 28% of deionized water and all the antibacterial quaternary ammonium salt monomers.

[0033] In the present invention, methyl methacrylate, 2-ethylhexyl acrylate and hydroxyethyl acrylate all contain stabilizer 4-methoxyphenol MEHQ, and the stabilizer needs to be removed by basic alumina before emulsification, and the mesh number of the basic alumina is either 100 mesh or 200 mesh.

[0034] In a second aspect, the present invention provides an antibacterial fluorescent acrylic coating, comprising a fluorescent antibacterial acrylic emulsion and an aqueous isocyanate curing agent, wherein the fluorescent antibacterial acrylic emulsion is as described above. The -NCO group in the aqueous isocyanate curing agent reacts with the -OH group on the acrylic resin molecular chain to form a carbamate, thereby capping the acrylic acid hydroxyl group and improving the comprehensive performance of the coating.

[0035] When preparing the coating, add a water-based isocyanate curing agent to the fluorescent antibacterial acrylic emulsion according to the molar ratio of -NCO to -OH of 1.5:1-2:1, and stir for 5 minutes until it is completely dissolved. The coating is applied to the surface of a substrate (tinplate sheet or glass slide), and an antibacterial coating with a film thickness of 200 to 300 μm is prepared through cross-linking and curing.

[0036] When operating in the laboratory, in order to save time, after brushing, the substrate is left to dry for 30 minutes and then transferred to the oven. The oven temperature is set to 80°C and the heating curing time is 1 hour. After heating, it is left to stand at room temperature for 24 hours before performance testing can be carried out.

[0037] Compared with the existing method, the present invention has the following advantages:

[0038] Compared with solvent-based paints, the co-solvent of water-based acrylic paints is water, and there is no VOC emission when used, which minimizes the harm to the environment and human health.

[0039] Compared with the traditional addition of slow-release antimicrobial agents, the present invention selects cations and ROS (generated by AIE fluorescent molecules) to jointly fight bacteria to make antimicrobial coatings, which has the following advantages: (1) Broad-spectrum antibacterial: Cationic antimicrobial agents and ROS can be effective against most bacteria and microorganisms. Rapid action: ROS can quickly destroy the cell structure of microorganisms, and the effect is relatively rapid; (2) Low risk of drug resistance: Cations and ROS antibacterial reduce the production of drug-resistant strains and can maintain a longer-lasting effect than traditional antimicrobial agents; (3) Persistence: Cationic antimicrobial agents can form a persistent antibacterial layer on the surface, improving the long-term effect; (4) Environmental protection: The chemicals commonly used in cations and ROS do not release toxic substances, which is more environmentally friendly and reduces the environmental burden.

[0040] Compared with the traditional method of detecting the antibacterial properties of coatings, the present invention provides a convenient detection method that does not require professional biological laboratory testing and uses the fluorescence change of the coating to reflect the change in the antibacterial properties of the coating. When bacteria and other microorganisms adhere and proliferate on the coating, causing the internal three-dimensional structure of the coating to be destroyed, the physical structure of the AIE fluorescent small molecules changes, and the fluorescence intensity changes accordingly, thereby showing the changes in the structure and antibacterial properties of the coating during the microbial corrosion process. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The transmission electron micrographs of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic emulsion provided in Example 1 of the present invention show that the emulsion microspheres have no obvious changes before and after modification, and are all complete and uniform spherical shapes;

[0042] Figure 2 The particle size distribution diagram of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic emulsion provided in Example 1 of the present invention: the particle size of the cationic acrylic emulsion is about 140 nm, and after the fluorescent molecules with larger molecular weight are polymerized and grafted on the molecular chain, the particle size of the emulsion increases to about 185 nm;

[0043] Figure 3 The zeta potential of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention: the potential of the cationic acrylic emulsion is +31.4 mv, and the potential increases to +40.1 mv after modification with the AIE small molecule with quaternary ammonium. The higher positive potential gives the coating excellent sterilization performance.

[0044] Figure 4Ultraviolet absorption and fluorescence spectra of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention: The fluorescence intensity test of the coating is carried out by quantitatively analyzing the fluorescence intensity of the cured coating by an Eclipse fluorescence spectrophotometer, selecting a light with a wavelength of 400nm to excite the sample, and recording the functional relationship between the fluorescence emission intensity generated by the coating and the emission wavelength, so as to obtain the fluorescence emission spectrum.

[0045] Figure 5 Optical photographs of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention taken under ultraviolet light excitation. The fluorescence intensity of the coating was measured by a portable ultraviolet analyzer WFH-204B, and the sample was irradiated at a wavelength of 365 nm, and then the luminescence intensity of the sample was observed. The modified emulsion showed obvious fluorescence;

[0046] Figure 6 The optical photographs of the coatings after curing of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention under ultraviolet light excitation are taken. The fluorescence intensity of the coatings is measured by a portable ultraviolet analyzer WFH-204B, and the coatings are irradiated at a wavelength of 365 nm, and then the luminescence intensity of the coatings is observed. The modified coatings show obvious fluorescence, indicating that the coatings have an indicating function;

[0047] Figure 7 This is a diagram showing the antibacterial effects of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The following examples and experimental examples are provided to further illustrate the present invention and should not be construed as limiting the present invention. The examples do not include a detailed description of conventional methods, which are well known to those skilled in the art and are described in many publications.

[0049] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the present invention, and the preferred implementation methods and materials described in the specific embodiments are for demonstration purposes only.

[0050] 1. Preparation of fluorescent cationic acrylic coating

[0051] Example 1

[0052] Step 1: Synthesis of fluorescent cationic acrylic emulsion

[0053] Weigh 0.5 g each of nonionic emulsifier OP-10 and cationic emulsifier hexadecyl dimethyl benzyl ammonium chloride, 65 mg of initiator AIBA, and 11.6 g of deionized water and mix them evenly to prepare the emulsifier part of the pre-emulsion. Weigh all 17.58 g of methyl methacrylate, 10.41 g of 2-ethylhexyl acrylate, 0.5 g of hydroxyethyl acrylate, and 15 mg of AIE fluorescent molecules and mix them evenly, then add them dropwise to the emulsification in step (1). The dropwise addition process lasts for about 20 minutes. After the dropwise addition is completed, stir at high speed for 30 minutes until the pre-emulsion presents a stable light yellow color and does not delaminate after being left for more than 30 minutes. The preparation of the pre-emulsion is completed. Weigh 30.085 g of deionized water, 0.15 g of disodium hydrogen phosphate, 0.2 g of OP-10, 0.2 g of hexadecyl dimethylbenzyl ammonium chloride emulsifier and 35 mg of initiator AIBA, mix well and add to a three-necked flask, heat to 75 °C, and condense and reflux. Add 10% of the total weight of the pre-emulsion, about 4 g, and drop the AIBA aqueous solution at the same time. Observe whether the three-necked flask turns blue. The whole process lasts for about 20-30 minutes. After the emulsion in the three-necked flask in step (3) turns blue, heat it to 78 °C, and start to drop the remaining pre-emulsion and the initiator AIBA aqueous solution (0.1 g AIBA dissolved in 16.1 g deionized water, and then add 1.875 g of cationic monomer) at a uniform speed. During this process, keep the temperature at 78 °C. The dropping process lasts for 2-2.5 hours. After the dropwise addition is completed, keep the temperature unchanged and continue to react for 30 minutes, then increase the temperature to 85 °C and continue to react for 30 minutes. After the reaction is finished, the system is cooled to below 40°C and the material is discharged to obtain a fluorescent cationic acrylic emulsion. The gel in the emulsion obtained in the experiment is filtered through a filter, weighed, and the gel fraction is calculated.

[0054] Step 2: Preparation of fluorescent cationic acrylic curing coating

[0055] Weigh 5 g of the fluorescent cationic acrylic emulsion synthesized in step 1, add 91 mg of water-based isocyanate curing agent to it, and ensure that the molar ratio of -NCO to -OH is 1.6:1. Stir for five minutes until it is uniform, and brush the emulsion onto the pre-treated substrate, which is a tinplate sheet or a glass slide. After drying at room temperature for 30 minutes, transfer to the oven, set the condition to 80℃ / 1 hour, and after heating, let it stand at room temperature for 24 hours before performing performance testing.

[0056] The specific processes of Comparative Example 1 and Examples 2-4 are the same as those of Example 1, except that the proportions of the components are different, as shown in Table 1 below:

[0057] Table 1 Summary of the proportions of comparative examples and embodiments

[0058] Serial number Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Glass transition temperature 30 ℃ 30 ℃ 30 ℃ 30 ℃ 30 ℃ Cationic monomer amount 0 5% 5% 5% 5% AIE small molecule to monomer ratio 0 1:500 1:1000 1:2000 1:5000

[0059] 2. Performance Test

[0060] 1. SEM inspection

[0061] The acrylic emulsion in comparative example 1 and the antibacterial fluorescent acrylic emulsion in example 1 were observed using a transmission electron microscope. The results showed that the acrylic emulsion (upper) and the fluorescent acrylic emulsion (lower) showed no significant changes in the emulsion microspheres before and after modification, and both were complete and uniform spherical ( Figure 1 ).

[0062] 2. Particle size and potential detection

[0063] Figure 2 The particle size distribution diagram of the cationic acrylic emulsion provided in comparative example 1 and the fluorescent cationic emulsion provided in embodiment 1 of the present invention is shown. The results show that the particle size of the cationic acrylic emulsion is about 140 nm, and after the fluorescent molecules with larger molecular weight are polymerized and grafted on the molecular chain, the particle size of the emulsion increases to about 185 nm.

[0064] Figure 3 The zeta potential of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention are shown. The results show that the potential of the cationic acrylic emulsion is +31.4 mv, and the potential increases to +40.1 mv after modification with the AIE small molecule with quaternary ammonium. The higher positive potential gives the coating excellent sterilization performance.

[0065] 3. Fluorescence detection

[0066] Fluorescence intensity test of the coating The fluorescence intensity of the cured coating was quantitatively analyzed by an Eclipse fluorescence spectrophotometer. The sample was excited by light of 400 nm wavelength and the functional relationship between the fluorescence emission intensity and the emission wavelength generated by the coating was recorded to obtain the fluorescence emission spectrum.

[0067] Figure 4 The UV absorption and fluorescence spectra of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention are shown. The results show that the absorbance of the acrylic emulsion after fluorescence and cationic modification shifts and generates fluorescence.

[0068] Figure 5 The optical photographs taken under ultraviolet light excitation of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention are shown. The fluorescence intensity of the coating is measured by irradiating the sample with a wavelength of 365 nm using a portable ultraviolet analyzer WFH-204B, and then observing the luminescence intensity of the sample. The modified emulsion exhibits obvious fluorescence.

[0069] Figure 6The optical photographs taken of the coatings after curing of the cationic acrylic emulsion provided in Comparative Example 1 of the present invention and the fluorescent cationic acrylic emulsion provided in Example 1 of the present invention under ultraviolet light excitation are shown. The fluorescence intensity of the coating is irradiated with a wavelength of 365 nm by a portable ultraviolet analyzer WFH-204B, and then the luminous intensity of the coating is observed. The modified coating exhibits obvious fluorescence, indicating that the coating has an indicating function.

[0070] 3. Technical Effect Verification

[0071] The fluorescent cationic acrylic emulsion embodiments of the present invention were subjected to the following tests, namely, a cross-hatch tape peeling adhesion test, an antibacterial and antifouling test, and the like.

[0072] 1. Adhesion test---frame tape peeling test

[0073] A 25 mm×75 mm×1 mm glass slide was pretreated, cleaned and dried, and then coated with the cationic high-solid low-viscosity acrylic resin coating synthesized in Comparative Example 1 and Examples 1 to 4, baked at 100° C. for 1-2 hours, and then allowed to stand in a dry environment for 2 hours for use.

[0074] Use a grid drawer to draw a pattern with a spacing of 1 mm × 1 mm on the coating, quickly stick the tape on the scratch, press until it is fully in contact, then tear off the tape, observe the coating damage, and grade the coating adhesion. The grading standards are as follows:

[0075] Grade 0B: The peeling area of ​​paint is greater than 65%; Grade 1B: The peeling area is greater than 35% and less than 65%; Grade 2B: The peeling area is more than 15% and less than 35%; Grade 3B: The peeling area of ​​the edges of the cut and intersection is greater than 5% and less than 15%; Grade 4B: The actual damage in the grid area is less than or equal to 5%; Grade 5B: There is no peeling on the edge of the grid, and the edge of the cut is completely smooth. This is the highest level of adhesion.

[0076] The results are shown in Table 2 below:

[0077] Table 2 Test results of fluorescent cationic acrylic emulsion in Example

[0078] Example Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Adhesion 3B 4B 4B 4B 4B

[0079] The results show that the coating adhesion obtained after the acrylic emulsions of Examples 1-4 were cured with isocyanate was all above 3B, showing excellent adhesion to the substrate.

[0080] 2. Antibacterial and antifouling test

[0081] The plate antibacterial test method was used. Bacteria selection: Escherichia coli (E. coli) was used as a Gram-negative (Gram -) bacterial model strain, and Staphylococcus aureus (S. aureus) was used as a Gram-positive (Gram +) bacterial model strain for antibacterial experiments.

[0082] Experimental grouping: In the antibacterial experiment, the OD value of the bacterial stock solution was 0.1 (10 8 CFU / mL), Escherichia coli or Staphylococcus aureus were divided into three groups: (I) bacteria + PBS, (II) bacteria + CA (the stock solution was diluted 15 times), and (III) bacteria + AIE-CA (the stock solution was diluted 15 times to [AIE] = 1*10 -5 mol / L).

[0083] Experimental conditions: All groups were exposed to white light for 1 hour. The total volume of each tube was 1 mL. After 1 hour of irradiation, the irradiated bacterial solution was diluted 10 4 times, take 100 μL of it and spread it evenly on the agar plate, and inoculate and culture it at 37°C for 12 hours to observe the colony formation.

[0084] Figure 7 The antibacterial effects of PBS, 10-fold diluted cationic emulsion and 10-fold diluted fluorescent cationic emulsion were shown. There was almost no bacterial colony growth on the surface of the emulsion culture medium, indicating that it had excellent sterilization performance.

[0085] The unexplained parts involved in the present invention are the same as the prior art or are implemented by the prior art. The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A fluorescent antibacterial acrylic emulsion, characterized in that: Including acrylic acid monomer, AIE fluorescent small molecule, antibacterial quaternary ammonium salt monomer, non-ionic emulsifier, cationic emulsifier, initiator, stabilizer and deionized water. In parts by weight, the acrylic monomer composition is as follows: 25-30 parts of methyl methacrylate MMA, 12-16 parts of 2-ethylhexyl acrylate 2-EHA, and 1.5%-2% of hydroxyethyl acrylate HEA; The content of the AIE fluorescent small molecule is 1‰-5‰ of the total amount of acrylic acid monomer, 2-5 parts of antibacterial quaternary ammonium salt monomer, 1-2 parts of non-ionic emulsifier, 1-2 parts of cationic emulsifier, initiator accounts for 0.8%-1.2% of the total weight of all monomers, 1-2 parts of stabilizer, and 90-100 parts of deionized water; the total weight ratio of all components is 100%.

2. The fluorescent antibacterial acrylic emulsion according to claim 1, characterized in that: The antibacterial quaternary ammonium salt monomer is a cationic monomer selected from an 80% aqueous solution of acryloyloxyethyl trimethyl ammonium chloride; The nonionic emulsifier is selected from any one or more combinations of OP-10, isomeric tridecanol polyoxyethylene ether (E1309), and 2535 nonionic emulsifier; The cationic emulsifier is selected from any one of hexadecyl dimethyl benzyl ammonium chloride and hexadecyl trimethyl ammonium bromide; The stabilizer is selected from one or both of disodium hydrogen phosphate and dipotassium hydrogen phosphate; The initiator is selected from azobisisobutyramidine hydrochloride V50.

3. The method for preparing the fluorescent antibacterial acrylic emulsion according to claim 1 or 2, characterized in that: The steps include: (1) Weigh some nonionic emulsifier, cationic emulsifier, initiator, and deionized water and stir them evenly to prepare the emulsifier part of the pre-emulsion; (2) Weigh all the methyl methacrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate and AIE fluorescent small molecule, mix them evenly, and then add them dropwise to the emulsification in step (1). After the addition is completed, stir at a high speed until the pre-emulsion presents a stable light yellow color and does not delaminate after standing for a period of time, thereby completing the preparation of the pre-emulsion; (3) Weigh a certain amount of deionized water, stabilizer, remaining nonionic emulsifier and cationic emulsifier, and part of the initiator to prepare a primer solution. After mixing the solution except the initiator evenly, add it into the reaction container, heat it to 75°C, and condense it under reflux. Add 10% of the total weight of the pre-emulsion, and start adding the initiator dropwise at the same time. Observe whether the reaction container turns blue. (4) After the emulsion in the reaction container turns blue in step (3), the remaining pre-emulsion and the initiator mixed aqueous solution prepared from the initiator and the antibacterial quaternary ammonium salt monomer are added dropwise at a uniform rate, and the temperature is raised to 78° C. and maintained constant during the process; (5) After the addition is completed, the temperature is maintained constant and the reaction is continued for 30 minutes, then the temperature is increased to 85°C and the reaction is continued for 30 minutes; (6) After the reaction is completed, the system is cooled to below 40°C and the material is discharged to obtain a fluorescent cationic acrylic emulsion. The gel in the emulsion obtained from the experiment is filtered through a filter, weighed, and the gel fraction is calculated.

4. The method for preparing the fluorescent antibacterial acrylic emulsion according to claim 3, characterized in that: Deionized water accounts for 15%-20% of the total water in the pre-emulsion, 50%-60% of the total water in the primer, and 22%-30% of the total water in the initiator mixed aqueous solution; The emulsifier in the pre-emulsion accounts for 70-75% of the total emulsifier, and the emulsifier in the primer accounts for 25-30% of the total emulsifier; The initiator in the pre-emulsion accounts for 30-35% of the total amount of initiators, the initiator in the primer accounts for 15-20% of the total amount of initiators, and the initiator in the initiator mixed aqueous solution accounts for 50% of the total amount.

5. The method for preparing the fluorescent antibacterial acrylic emulsion according to claim 3, characterized in that: In step (1), 71.4% of nonionic emulsifier, 71.4% of cationic emulsifier, 32.5% of initiator, and 20% of deionized water are weighed to prepare the emulsifier part of the pre-emulsion; In step (2), the emulsification dropwise addition process lasts for about 20 minutes. After the dropwise addition is completed, stirring is performed at a speed of more than 800 r / min for 30 minutes until the pre-emulsion exhibits a stable light yellow color and does not delaminate when left standing for more than 30 minutes, thereby completing the preparation of the pre-emulsion.

6. The method for preparing the fluorescent antibacterial acrylic emulsion according to claim 4, characterized in that: In step (3), 52% of deionized water, all stabilizers, remaining nonionic emulsifiers and cationic emulsifiers are weighed, mixed evenly, added to a reaction vessel, heated to 75°C, and condensed and refluxed; 10% of the total weight of the pre-emulsion is added, and at the same time, a solution prepared with 17.5% initiator is started to be added dropwise, and the reaction vessel is observed to see whether it turns blue; In step (4), the mixed aqueous solution of the initiator and the antibacterial quaternary ammonium salt monomer is prepared by the remaining 50% of the initiator, 28% of deionized water and all the antibacterial quaternary ammonium salt monomers.

7. The method for preparing acrylic resin according to claim 6, characterized in that: In step (3), if there is still no sign of blueing 20 minutes after the addition of the pre-emulsion, the temperature of the reactor is raised by 1-2°C and the initiator aqueous solution is added dropwise at a rate of about 0.2 ml / min until the solution turns blue before proceeding to the next step.

8. An antibacterial fluorescent acrylic paint, characterized in that: It comprises a fluorescent antibacterial acrylic emulsion and an aqueous isocyanate curing agent, wherein the fluorescent antibacterial acrylic emulsion is as described in any one of claims 1 to 7; Add water-based isocyanate curing agent to the fluorescent antibacterial acrylic emulsion according to the molar ratio of -NCO to -OH of 1.5:1-2:1, and stir for 5 minutes until it is completely dissolved.

9. The antibacterial fluorescent acrylic paint according to claim 8, characterized in that: The coating is applied to the surface of a substrate, and is cross-linked and cured to prepare an antibacterial coating with a film thickness of 100 to 200 μm.

Citation Information

Patent Citations

  • Fluorescent nano-microsphere with pH responsiveness and AIE (aggregation induced enhanced emission) property and application of fluorescent nano-microsphere

    CN106084110A

  • High-hydroxyl acrylic emulsion with quick drying and long working life and synthesis method thereof

    CN111807961A

  • Cationic polyacrylate antibacterial emulsion and preparation method thereof

    CN115160484A

  • Aqueous AIE fluorescent anti-counterfeiting emulsion as well as preparation method and application thereof

    CN118085160A

  • Acrylic coating with fluorescent effect

    CN118109099A

Cited By

  • Antibacterial light-cured resin composition as well as preparation method and application thereof

    CN122080321A

  • An antibacterial photocurable resin composition, a method of preparing the same, and an application thereof

    CN122080321B